Incidence and Quantification of Fumonisins B1 and B2 at Harvest Stage in Sorghum - SHARMA, MANJU; MONTES, R.; M-RQUES, C.; BRAVO, L.L.; FLORES, M.H.E. (Asian Journal of Chemistry, 2010)
Mycotoxins produced by Fusarium species particularly Fusarium moniliforme is a major concern in maize, millet, sorghum and agricultural products. A field experiment of sorghum with four different sowing dates with six replications was undertaken in the community of Tlayca (Morelos, Mexico) for the determination of fumonisins B1 and B2. Quantifications of these fumonisins in sorghum samples were done using reversed phase HPLC with fluorescence detection and OPA (o-phthaldialdehyde/2-mercaptoethanol) derivating method at λex 370/λem 418 run. Detection limit was 20 ppb for both fumonisins at a signal to noise ratio of 4 : 1 To the best of our knowledge this report appears to be the first study on the quantitative determination of FB1 and FB2 in sorghum. Mean recoveries of FB1 and FB2 were 99.6 and 91.8% with relative standard deviation of < 4 and < 3 from spiked samples of sorghum respectively. In conclusion, total fumonisin levels do not exceed the recommended tolerance levels whereas temperature and weather conditions were critical factors affecting the fungal infection and fumonisin synthesis during the sorghum sowing dates.